2011
DOI: 10.1159/000334477
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Discovery in Serum from Patients with Carotid Atherosclerosis

Abstract: Background: Blood-based biomarkers of atherosclerosis have been used to identify patients at high risk for developing stroke. We hypothesized that patients with carotid artery disease would have a distinctive proteomic signature in blood as compared to a healthy control population without carotid artery disease. In order to discover protein biomarkers associated with increased atherosclerotic risk, we used two different strategies to identify biomarkers from patients with clinically defined atherosclerosis who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Moreover, it has been observed that IPH in carotid lesions can predict adverse events in other vascular territories, which underlined the notion that it should be investigated as a target for noninvasive imaging and diagnostic approaches (33) . We recently demonstrated that Hb-haptoglobin (Hp) binding as well as Hb metabolism were some of the most enriched functional categories in a global transcriptomic analysis of carotid plaques and peripheral blood mononuclear cells (11) , and the importance of Hb metabolism in unstable atherosclerosis has also been supported by epidemiological findings linking a common genetic variant of Hp to cardiovascular risk 34 , 35 , 36 . Here, the notion that IPH and Hb metabolism are central elements in end-stage unstable carotid atherosclerosis was confirmed as enrichment of many IPH-related molecules was found in plaques, whereas BLVRB was the only component of this pathway significantly reflected in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been observed that IPH in carotid lesions can predict adverse events in other vascular territories, which underlined the notion that it should be investigated as a target for noninvasive imaging and diagnostic approaches (33) . We recently demonstrated that Hb-haptoglobin (Hp) binding as well as Hb metabolism were some of the most enriched functional categories in a global transcriptomic analysis of carotid plaques and peripheral blood mononuclear cells (11) , and the importance of Hb metabolism in unstable atherosclerosis has also been supported by epidemiological findings linking a common genetic variant of Hp to cardiovascular risk 34 , 35 , 36 . Here, the notion that IPH and Hb metabolism are central elements in end-stage unstable carotid atherosclerosis was confirmed as enrichment of many IPH-related molecules was found in plaques, whereas BLVRB was the only component of this pathway significantly reflected in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Hb-Hp complex was one of the most enriched GO categories in plaques and Hb metabolism was enriched in PBMCs. A common genetic variant of Hp has recently been associated with cardiovascular disease risk in multiple independent cohorts, both in plaques and in peripheral blood [56][57][58], and Hp genotyping has been recommended for risk identification and treatment optimization [56].…”
Section: Discussionmentioning
confidence: 99%
“…In the current view, accumulating evidences support a critical role for inflammation in the pathogenesis of atherosclerosis. Several studies have demonstrated that C-reactive protein [ 4 , 5 ], B-type natriuretic peptide (NT-pro-BNP) [ 6 ], and serum cardiac troponin I (cTN-I) [ 7 ] as robust serum biomarkers for CAD risk.…”
Section: Introductionmentioning
confidence: 99%